Stability of triangular points in the relativistic R3BP when the bigger primary is an oblate spheroid. Issue 1 (2nd January 2016) - Bello, Nakone; Singh, Jagadish
Abstract: In this paper, we study the effect of oblateness of the more massive primary in the relativistic R3BP. We observe that the locations of the triangular points and their stability are affected by the relativistic and oblateness factors. It is also noticed that the oblateness factor possesses destabilizing behavior. Therefore, the size of the region of stability decreases with increase in the value of the oblateness factor. Further, a numerical study on the locations of the triangular points and the critical mass for the Earth-Moon, Jupiter and its Moons, Saturn and its Moons systems is given.